Kemenangan Pasangan Calon Mundjiri-Ngesti dalam Pemilihan Umum Bupati dan Wakil Bupati Kabupaten Semarang Tahun 2015 - Astrida Ulfa Aninda; Lusia Astrika (Journal of Politic and Government Studies, 2018)
The election of regional heads of Semarang regency in 2015 was participated by two candidates in which one of the candidates was an incumbent from the previous regent, Mundjirin. Mundjirin is accompanied by Ngesti Nugroho who is a cadre and DPC’s chairman of the carried party that is PDI Perjuangan. Besides being carried by a party with a big mass base in Semarang regency, Mundjirin-Ngesti is also supported by two other parties namely PAN and Partai Gerindra. Mundjirin-Ngesti earned 65% of the vote, that is appealing,  while major parties, who supported them, only managed to break through 41.72% in legislative elections in 2014 when the vote was combined.The purpose of this research is to analyze the role of political party machine and figure, where the party with big mass base is expected to contribute greatly to the victory of the candidate besides the candidate has their own figuration. The method used in this research is a qualitative method. Primary data from this research was obtained directly from an interview with informant through purposive sample and snowball sampling technique. While secondary data obtained indirectly through documents, articles, mass media, internet, and other literature studies. The data has been obtained then compiled with the stages of reviewing data, analyzing data and drawing conclusions and data verification. Thus, it yields descriptive data to illustrate the results of winning analysis of Mundjirin-Ngesti pair.Based on the results of research in the field, the most dominant role in the process of winning is the figure of Mundjirin-Ngesti itself mainly from social capital and economic capital owned. Party, as a vehicle of the candidate to win the election of the regional head, is less able to contribute greatly to the couples it supports. However, due to political marketing and figures with established social capital and economic capital, Mundjirin-Ngesti is able to win the election of regional heads of Semarang Regency in 2015.With the election of Mundjirin-Ngesti as the winner in the regional head election, they are expected to fulfill the promise of politics that is to strengthen Semarang regency to become Advanced, Independent, Discipline and Prosperous. Similarly, for political parties, that supported, are expected in the future to always guard Mundjirin-Ngesti during their term, if there is a policy that deviates from the goal of prospering the public, they will become the first party in giving reprimand and criticism. Key Words: Victory of Regional Head Election, Figure, Political Party, Political Marketing